(3GdeOhfI aj Gdabg GdeGdcis - (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj,J (B191 (3g` s; (3QhGjI SMfhf Hf SYjO GdJfhMis
(3ChdgG (B:s
(3GdYed ai GdhVhA bdJ dGHf GdbGSe (B: (3CQGjJ GdhVhA CcGf eGdc jhbJ ajg hGMOI Ch GKfJjf Ch KdGKkG? s
(3BNQgG (B:s
(3jfJgi HeG LGA ai GdebGe ef cJGH GdML GdChd s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3fSNI Ydi Qb ZRGds
(3ai SHYI CLRGA MOjKjI hQO GdYfhGf GdCUdi ai cX (B2/ 1644 s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3Gdabg GdeGdcjs